PENILAIAN ORGANOLEPTIK FERMENTASI PAKAN KOMPLIT TERNAK KAMBING BERBASIS PUTAK DAN TEPUNG IKAN - bambang hadi sutanto (Politeknik Pertanian Negeri Kupang, 2019)
This study aims to utilize the availability of local food such as gamal leaves, corn klobot, putak, rice bran and fish meal through a touch of fermentation technology. The design used in this study was a completely randomized design with 4 treatments and 5 replications. This study assessed organoleptic fermentation of complete feed with 0, 3, 6 and 9 weeks fermentation time in anaerobic conditions with organoleptic research variables (color, aroma, texture) Organoleptic results showed that the fermentation period of 3 weeks and 6 weeks (33.3%) showed the brightest color of complete fermented feed, 9 weeks fermentation time showed the most preferred aroma level (55.5%), 6 weeks fermentation time showed texture the softest (55.5%). The conclusion of acceptance of complete feed fermentation time to color, aroma and texture was fermentation time for 6 weeks (44.4%).